King Alfred and the Danish wars in Anglo-Norman histories - Winkler, EA (V&R unipress, Bonn University Press, 2020)
This paper asks howand why Anglo-Normanwriters in England (c. 1120–1150) narrated the Danish wars of the late ninth century and King Alfred’s role as a military general. It examines their accounts of defensive maneuvers in which Alfred was engaged against the Danes, both before and during his reign, in particular the key points at which these chroniclers deviated visibly from their sources. Several of these literary changes have been seen as points of clarification or as embellishments, but they actually effect material changes in historical perspective. Unlike later encomiasts of Alfred, these chroniclers wrote about Alfred’s experiences of warfare without drawing significantly on hindsight or evaluating his actions in light of their ultimate outcomes. Instead, they elaborated on moments of disorder and crisis. By amending the narrator’s temporal location in the narrative, and choosing a vantage point closer to the events and people they described, they sought to adopt the participants’ lack of foreknowledge of the future.